Behavioural and demographic factors associated with occurrence of non-melanoma skin cancer in organ transplant recipients - Fania, Luca; Abeni, Damiano; Esposito, Ilaria; Spagnoletti, Gionata; Citterio, Franco; Romagnoli, Jacopo; Castriota, Marina; Ricci, Francesco; Moro, Francesco; Perino, Francesca; Mazzanti, Cinzia; De Simone, Clara; et al. (Giornale italiano di dermatologia e venereologia : organo ufficiale, Societa italiana di dermatologia e sifilografia, 2020)
Non-melanoma skin cancers (NMSC) are the most common epithelial malignancies in organ transplantation recipients (OTRs). In Italy, incidence rates of post- transplantation NMSC are approximately 5% after 5 years and 10% after 10 years since organ transplantation. The objective was to describe risk factors associated with NMSC in a cohort of renal and liver transplant recipients, in a single-center longitudinal study. Renal and liver transplant patients, who underwent transplantation between June 1985 and December 2015, were visited for the first time or followed-up in a dedicated outpatient clinic every six months until July 2016. We included 356 renal and 76 liver transplant patients. 108 OTRs (25.6%) presented 299 NMSC. 74 patients developed actinic keratosis (17.1%), 36 patients squamous cell carcinoma (8.5%), and 52 patients basal cell carcinoma (12.3%). Time from transplantation and kidney transplant were the main risk factors for NMSC. Higher incidences of all NMSC were observed in patients >60 years, males and smokers, while decreased incidences were detected in individuals with higher educational levels. Multiple logistic regression models confirmed that male gender (RR 3.3, P=0.001), cigarette smoking (RR 2.0, P=0.026), light eye color (RR 2.9, P=0.001), and family history of cancer (RR 1.8, P=0.042) were independently associated with NMSC. Dermatological follow-up is important in OTRs, due to the higher risk of tumors and mainly NMSC. Clinical and environmental factors, including cigarette smoking, are useful in characterizing OTR with higher risk of NMSC.